The Need And Urgency of Human Resource Information System (HRIS) on MSMEs in Indonesia: A Literature Study - Sutikman; Lantana , Dhieka Avrilia; Digdowiseiso , Kumba (CV ODIS, 2023)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, but often face challenges in managing human resources. In this context, Human Resource Information Systems (HRIS) emerge as a potential solution to overcome this problem by automating various administrative and HR management tasks. This research aims to summarize literature studies related to the need and urgency of using HRIS in MSMEs in Indonesia. This research uses a literature study approach to analyze journals, books and research reports that are relevant in the context of HRIS and MSMEs in Indonesia. The results of the literature study show that MSMEs in Indonesia have various needs that can be met through the use of HRIS, including operational efficiency, better employee management, regulatory compliance, and enhanced competitiveness. The urgency of HRIS is reflected in increasing productivity, reducing administrative burdens, and improving the quality of HR management. This literature study confirms the importance of HRIS in supporting MSMEs in Indonesia in managing human resources more efficiently. The use of HRIS not only meets the current needs of MSMEs but also prepares them to compete in an increasingly complex and digital business environment. Therefore, implementing HRIS is a strategic step that needs to be considered by MSMEs in Indonesia to achieve sustainable growth